Beyond national culture difference: The role of cultural intelligence in cooperation within international construction joint ventures and insights from Chinese companies. Issue 7 (19th June 2019) - Cui, Zhipeng; Liu, Junying; Xia, Bo; Cheng, Yaxiao
Abstract : Purpose: International construction joint ventures (ICJVs) have been widely used as a temporary arrangement in many projects all over the world, especially in megaprojects. Within ICJVs, the national culture difference between partners affects their cooperation significantly. However, prior research has provided contradictory empirical evidence regarding these impacts. To address this problem, the purpose of this paper is to introduce cultural intelligence that judges an individual's capability to function and manage effectively in culturally diverse settings as a moderating variable. Design/methodology/approach: Multiple regression analysis and moderated multiple regression were undertaken to test proposed hypotheses. A questionnaire survey was conducted with international construction practitioners who had experiences of managing or participating in ICJVs. Findings: The result of multiple regression analysis revealed that difference in national culture has significant negative effects on information exchange, shared problem solving and flexibility when asking for changes, thus effecting cooperation within ICJVs. Meanwhile, cultural intelligence of members can weaken these negative influences. Practical implications: First, given that national culture difference affects negatively on the cooperation within ICJVs, it needs to be regarded as one of vital resources of risk which should be prevented and managed when attending ICJVs; Second, managers should build a series of mutually agreeable regulations and rules to lessen the negative effect of national culture difference; Third, it is recommended that ICJV management teams contain as many work-experienced members as possible and members within ICJVs, especially new staff, receive cross-cultural training termly to facilitate the cooperation between partners. Originality/value: This research reveals the moderating effects of cultural intelligence on the relationship between national culture difference and cooperation in ICJVs as well as provides practical implications for ICJV managers to deal with national culture difference and reduce its negative impact on cooperation within ICJVs.